A new species of Sobarocephala Czerny, 1903 (Diptera: Clusiidae) from Vietnam. (3rd July 2018) - Galinskaya, Tatiana Vladimirovna
Abstract: Sobarocephala is the most diverse genus of druid flies Clusiidae, known from all biogeographic regions. Two species, S. apoxys and S. triangula were known from Vietnam. Sobarocephala cattiensis sp.nov. from Vietnam is described and illustrated. The new species is close to S. megastylis and to S. cycla . This new species was collected in Cat Tien National park (Dong Nai Province), in a seasonal tropical forest. http://www.zoobank.org/urn:lsid:zoobank.org:pub:58CFBCD7-B876-4B09-9E17-5E70D0B586D7